Pengaruh Penambahan Lactobacillus fermentum CK165 dan Lama Fermentasi terhadap Karakteristik Fisik Kopi Arabika (Coffea arabica) Asal Kintamani, Bangli - Hatiningsih, Sayi; Mayun Permana, I Dewa Gde; Admadi Harsojuwono, Bambang; Wayan Gunam, Ida Bagus; Wahyu Adi, Noval (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p11, 2022)
The fermentation stage is considered to be one of the critical steps in coffee processing due to its impact on the final quality of the product. The aim of this study was to determined the effect of Lactobacillus fermentum CK165 addition and fermentation time on the physical characteristics of Arabica coffee Kintamani, Bangli, and knowing the right treatment to produce Arabica coffee with the best physical characteristics. This study used a completely randomized design (CRD) with treatment using Lactobacillus fermentum CK165 addition and duration of fermentation consisting of 0 hours, 12 hours, 24 hours, and 36 hours. Each treatment was repeated 2 times to obtain 16 experimental units. The physical characteristics of Arabica coffee were analyzed statistically by analysis of variance (ANOVA) and continued with Duncan multiple range test (DMRT), if there was an affect between treatments. The result showed that Lactobacillus fermentum CK165 addition and fermentation time significantly affected the bulk density, moisture content, bean number/10 g, weight of 100 beans, bean wide, and color (L* and b*). Lactobacillus fermentum CK165 addition and fermentation for 24 hours resulted Arabica coffee with the best physical characteristics with bulk density 0.637 g/ml, moisture content 8.507%, bean number/10 g 51.500 beans, weight of 100 beans 19.873 g, long 10.570 mm, wide 7.401 mm, thick 4.305 mm, L* 36.588, a* 1,670, b* 11.045, broken beans 0.533 bean number/100 g, brown beans 0.102 bean number/100 g, and partly black beans 1.766 bean number/100 g.